MODEL OF MANAGEMENT OF INDUSTRIAL ENTERPRISES ON THE BASIS OF CIRCULAR ECONOMY - Андрусів, Уляна Ярославівна; Зелінська, Галина Олексіївна; Дрінь, Наталія Ярославівна (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2024)
The role of the circular economy in the context of sustainable development of industrial enterprises of Ukraine has been studied. A model for making and coordinating management decisions based on circular economy for industrial enterprises is proposed. The model provides for the creation and reorganization of existing enterprises for the processing and use of waste as raw materials. For this purpose, economic instruments should be developed at the state level. They should stimulate at the expense of: funds, public procurement, capital investments in environmental protection, help in obtaining grant funds for joint implementation with the EU of investment business projects in the field of circular economy, preferential lending to small and medium-sized enterprises and consulting activities (creating an agency on the development of the circular economy in Ukraine) in accordance with national legislation and adopted EU directives. The first step for this is the implementation of a comprehensive waste management program, which provides for a wide range of measures to be implemented. The improved model for making and coordinating management decisions on the basis of the circular economy for industrial enterprises includes seven stages, which are based on a program-targeted approach that determines the regularities between the indicators of "waste management" and "volumes of waste", "emissions of pollutants" and " capital investments" in the system of interactions between the state, business, society and intermediaries. It has been established that for the implementation of the state policy in the implementation of the circular economy, it is necessary to take into account the interests of all interested parties who are directly or indirectly interested in the development of such a policy. An effectively established interaction between the state and business is a mechanism of economic growth and social well-being, and the effective direction of this process is public-private partnership (PPP) in terms of such components as: legal, institutional, organizational, economic.